EVALUATING IMPLEMENTATION OF E-GOVERNMENT PUBLIC SERVICES IN DKI JAKARTA TOWARDS A SMART CITY USING THE CIPP AND KIRKPATRICK EVALUATION MODEL - Pakpahan, Roy Tumpal (Universitas prof. Dr. Moestopo (Beragama), 2024)
This study evaluates the implementation of the E-Government program in DKI Jakarta using the CIPP (Context, Input, Process, Product) evaluation model and the Kirkpatrick model. The CIPP evaluation results indicate that the E-Government program has successfully integrated various public services into a digital system aligned with the Regional Medium-Term Development Plan (RPJMD). The program requires ongoing investment in information technology infrastructure and training for civil servants, as well as increased participation from various government agencies and the public. The product evaluation results show improved government transparency and accountability, making it easier for the public to access public services and government policy information. The evaluation using the Kirkpatrick model shows positive results at every evaluation level, with users providing positive feedback on e-government services, increased understanding, adoption of digital services, and significant long-term impacts on operational efficiency, transparency, and public satisfaction. However, this study also identifies challenges that need to be addressed, such as technology infrastructure gaps, digital literacy among the public, and data security and privacy issues. Addressing these challenges will optimize the implementation of E-Government in DKI Jakarta and support the government's vision of an efficient, inclusive, and responsive Smart City.